Pengaruh Konten Media Sosial Tiktok Terhadap Etika Akademik Mahasiswa Prodi KPI UIN SU - May Hasanah; Dwi Dini Farah Diva; Nur Aini; Rizki Cahya Wahyuni; Nasrullah Hidayat (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
The development of technology, particularly social media, has had a significant impact on society, including among students. TikTok, as one of the popular social media platforms, offers a diverse range of audiovisual content that can influence students' academic behavior. This study aims to examine the influence of TikTok content on the academic ethics of students in the Communication and Islamic Broadcasting Study Program at the State Islamic University of North Sumatra. The research method used is quantitative with a regression approach, involving 233 respondents. The results indicate a significant relationship between educational TikTok content and academic ethics, where exposure to educational content positively affects students' adherence to academic integrity principles. Conversely, content that undermines academic ethics has a negative impact, with 60% of respondents admitting to being influenced by TikTok content in their academic behavior. These findings emphasize the importance of students' understanding and awareness of the content they consume on social media, as well as the need for educational institutions to educate students about academic ethics in the digital age.